2019
DOI: 10.1063/1.5102162
|View full text |Cite
|
Sign up to set email alerts
|

Micro instabilities and rotating spokes in the near-anode region of partially magnetized plasmas

Abstract: Electron and ion transport in the near-anode region of a partially magnetized plasma under conditions typical of Hall thrusters or magnetron discharges is studied with fully kinetic, Particle-In-Cell Monte Carlo Collision (PIC-MCC) simulations assuming a uniform magnetic field and no ionization. We derive a simple relation that defines the magnetic field at the transition point between negative and positive sheath. For magnetic fields around or above this transition point, PIC-MCC simulations show the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
2
16
0
Order By: Relevance
“…The main results can be summarized as follows. 1) For sufficiently large magnetic fields, the modified Simon-Hoh instability 17 is likely to develop 40 in the region of decaying magnetic field between cathode and anode in magnetron discharges or between channel exhaust and anode in Hall thrusters. When self-consistent ionization is taken into account in the model, the PICC MCC simulation results show that the Simon-Hoh instability evolves into an ionization instability that rotates in the azimuthal direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main results can be summarized as follows. 1) For sufficiently large magnetic fields, the modified Simon-Hoh instability 17 is likely to develop 40 in the region of decaying magnetic field between cathode and anode in magnetron discharges or between channel exhaust and anode in Hall thrusters. When self-consistent ionization is taken into account in the model, the PICC MCC simulation results show that the Simon-Hoh instability evolves into an ionization instability that rotates in the azimuthal direction.…”
Section: Discussionmentioning
confidence: 99%
“…We studied in Ref. 16 anomalous electron transport across the magnetic field associated with the development of instabilities in the nearanode region, assuming a given ionization rate profile, and showed that Simon-Hoh instabilities 17,18 were likely to form for sufficiently large magnetic fields. In the present paper we present a self-consistent study of plasma transport in conditions typical to a magnetron discharge (Figure 1b) and show that the Simon-Hoh instability evolves into an ionization instability.…”
Section: Rotating Spokes In Magnetrons and Hall Thrustersmentioning
confidence: 99%
“…The two-dimensional (2D) PIC-MCC model described in previous papers 15,16,26 has been used to simulate this experiment. The simulation domain is defined by the axial and azimuthal directions ̂ and ̂.…”
mentioning
confidence: 99%
“…The main results can be summarized as follows. The small cross-field electron mobility is responsible for an instability (presumably of the Simon-Hoh type 3,26 in its initial phase) that leads to an azimuthal distortion of the plasma potential and density. This distortion allows some electrons to flow to the anode along an equipotential line connecting the cathode and anode regions.…”
mentioning
confidence: 99%
“…There were also attempts to identify the spoke nature by comparing the gradient drift instability theory with experiments performed in magnetron [32,33] and hybrid model (fluid electrons and kinetic ions) [34]. Further, 2D fully kinetic PIC/MCC simulations with Cartesian grid and artificial ionization were also performed to study micro instabilities and macroscopic structures in the near-anode region of a partially magnetized plasma under conditions typical of Hall thrusters or magnetron discharges [26]. In that work, a magnetic field threshold indicating the transition point between the positive sheath and the negative sheath was proposed, and the micro instability development was investigated for different magnetic fields with respect to the threshold value.…”
Section: Introductionmentioning
confidence: 99%